2013
DOI: 10.3109/09513590.2013.788627
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapeutic approach in early and late post-menopausal Brazilian women

Abstract: To evaluate changes in joints after physiotherapy in post-menopausal women, specifically to identify clinical responses to the measurements of flexibility, functional capacity and joint pain in early and late post-menopausal women at a multi-disciplinary health education programme. A total of 69 women participated in the Integral Program for the Attention to Climacteric Women at the Department of Gynecology - Federal University of Sao Paulo and were sorted into two groups of early (n = 32) and late (n = 37) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…In this context, physical exercise is a potent tool for health promotion and disease prevention; and the different types of training can be beneficial for menopausal women, such as aerobic training, resistance training combined training and, recently popular in the fitness industry, functional training …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, physical exercise is a potent tool for health promotion and disease prevention; and the different types of training can be beneficial for menopausal women, such as aerobic training, resistance training combined training and, recently popular in the fitness industry, functional training …”
Section: Introductionmentioning
confidence: 99%
“…4 By associating the changes induced by menopause and the deleterious effects caused by the natural aging process, such as decline in aerobic and functional capacity, 5 and muscle capacity to generate maximum force, as well as the deterioration of the sensory system, 6 we observed the need to seek ways to minimize the physiological loss in women arising from both processes. 7 In this context, physical exercise is a potent tool for health promotion and disease prevention; 8 and the different types of training can be beneficial for menopausal women, such as aerobic training, 5 resistance training 9,10 combined training 7,11 and, recently popular in the fitness industry, 12 functional training. 13,14 Functional training has been prepared from the imitation of everyday gestures and activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is known that age, overweight and obesity, smoking, and the presence of multi-morbidities impair the quality of life and impact the functional capacity. 9 According to Fonseca et al, the most relevant information in medical history declared at the time of the initial treatment in women after menopause were: hypertension (44.94%), diabetes (10.1%), smoking (8.39%), thyroid disorders (7.7%), malignancies (6.41%), cardiovascular disease (17.1%), dyslipidemia (0.88%) and psychiatric disorders (0.06%). 10 The severity of menopausal symptoms is negatively influenced in the presence of chronic diseases, multiple pregnancies and not using hormone therapy, with worsening of self-perceived health.…”
mentioning
confidence: 99%
“…5 Studies have demonstrated benefits for climacteric symptoms, particularly improvement in vasomotor symptoms, depressed mood, arthralgia and myalgia. 8,9 In female aging, effects in lower genital tract are common and related to late post-menopause, being atrophic vulvovaginitis and urogenital dysfunctions common complaints brought by patients. 15,16 Atrophic vulvovaginitis affects 40% of postmenopausal women.…”
mentioning
confidence: 99%
“…4,5,7 Research shows associations among obesity, menopausal symptoms and worse quality of life. 5,[8][9][10][11][12][13][14][15][16][17] To conduct this evaluation, various types of questionnaires are used, both generic -analyzing overall quality of life for any population -and specific questionnaires to analyze the quality of life in the transition to menopause and postmenopause. [18][19][20][21] The objective of this work is to identify the instruments used to measure the quality of life of overweight and obese women in climacteric age (during the transi-tion to menopause and post-menopause), through a systematic review of the literature.…”
Section: Introductionmentioning
confidence: 99%